“I think I use them, but I’m not sure what each one is called”: integration of multiple literacies in secondary social studies and science classes - Lickteig, Amanda D. (Kansas State University, 2015)
In the past, literacy was viewed solely as the basic, functional skills of reading and writing. However, with the New London Group’s (1996) proposal of multiliteracies and the more recent push for a plurality of literacies (NCTE, 2011), teachers have been urged to expand their definitions of literacy. This qualitative study explores how secondary-level social studies and science teachers perceive literacies and identifies their instructional literacies practices. Data were collected through a pre- and post-questionnaire, three focus group sessions, classroom observations, field notes, and artifacts. This study solicited nearly one hundred secondary social studies and science teachers from three Midwestern school districts. Eight educators (four social studies and four science) participated in the study that took place in the spring of 2015. Furthermore, a generous grant from a local chapter of Phi Delta Kappa partially funded this research. After applying initial and holistic codes to the data, nine themes emerged: conventional, progressive, hesitant/emerging, collaborate, calibrate, perform, practice, interdisciplinary, and intradisciplinary. The nine themes were further classified by how they appeared in the data: dispositional themes, behavioral themes, and bridge themes. Throughout the data analysis, contemporary genre theory guided the study (Devitt, 2004). Descriptive codes, derived from contemporary genre theory, further revealed that the situational, social, historical, and individual aspects of genre influence teachers’ pedagogical practices related to multiple literacies across disciplines. Therefore, the ways in which teachers perceived multiple literacies and implemented them into classroom instruction are multifaceted and vary depending on grade level, content area, and teaching location. However, teachers’ dispositions regarding literacy move beyond a traditional mindset of functional reading and writing as they engage in professional learning opportunities and collaborate within and across disciplines and grade levels. This study provides secondary educators insight into the prominence of multiple literacies present across content areas while also revealing the teaching methods and instructional strategies that foster multiple literacies.
Keywords: Contemporary genre theory; Focus groups; Multiple literacies; Secondary social studies teachers; Secondary science teachers; Education, General (0515); Reading Instruction (0535); Secondary Education (0533)